Identification of novel GLUT inhibitors. Issue 7 (1st April 2016) - Siebeneicher, Holger; Bauser, Marcus; Buchmann, Bernd; Heisler, Iring; Müller, Thomas; Neuhaus, Roland; Rehwinkel, Hartmut; Telser, Joachim; Zorn, Ludwig
Graphical abstract: Abstract: The compound class of 1 H -pyrazolo[3, 4- d ]pyrimidines was identified using HTS as very potent inhibitors of facilitated glucose transporter 1 (GLUT1). Extensive structure–activity relationship studies (SAR) of each ring system of the molecular framework was established revealing essential structural motives (i.e., ortho -methoxy substituted benzene, piperazine and pyrimidine). The selectivity against GLUT2 was excellent and initial in vitro and in vivo pharmacokinetic (PK) studies are encouraging.